Detection and identification of -GlcNAc-modified proteins using 6-azido-6-deoxy--acetyl-galactosamine - Guo, Jianshuang; Zhang, Guoqiang; Ma, Jing; Zhao, Caili; Xue, Qingqing; Wang, Jiyan; Liu, Wenjie; Liu, Kaihui; Wang, Haifeng; Liu, Ning; Song, Qitao; Li, Jing (Organic & biomolecular chemistry, 2019)
An unnatural monosaccharide with a C6-azide, Ac 3 6AzGalNAc, has been developed as a potent and selective probe for O -GlcNAc-modified proteins. Combined with click chemistry, we demonstrate that Ac 3 6AzGalNAc can robustly label O -GlcNAc glycosylation in a wide range of cell lines. Meanwhile, cell imaging and LC-MS/MS proteomics verify its selective activity on O -GlcNAc. More importantly, the protocol presented here provides a general methodology for tracking, capturing and identifying unnatural monosaccharide modified proteins in cells or cell lysates. Ac 3 6AzGalNAc, as a metabolic probe, can robustly label O -GlcNAc-modified proteins in cells with high selectivity.